Defect assisted room temperature ferromagnetism on rf sputtered Mn doped CeO2 thin films. Issue 1 (January 2017) - Murugan, R.; Vijayaprasath, G.; Thangaraj, M.; Mahalingam, T.; Rajendran, S.; Arivanandhan, M.; Loganathan, A.; Hayakawa, Y.; Ravi, G.
Abstract: Pure and manganese doped cerium oxide (CeO2 & Mn-CeO2 ) thin films were deposited on glass substrates by employing rf magnetron sputtering having CeO2 and Mn-CeO2 targets. Deposited films were characterized by using X-ray diffractometer (XRD), X-ray photoelectron spectroscopy (XPS), photoluminescence (PL), atomic force microscope (AFM) and vibrating sample magnetometer (VSM). XRD patterns reveal the single crystalline nature of films with oriented growth in (220) plane and peak shift to the lower angles for the Mn doped CeO2 films. Mn doped cerium oxide exhibits strong luminescence at ~490–520 nm, possibly due to defects like oxygen vacancy created by Mn doping. Oxygen vacancy is responsible for ferromagnetic property of Mn doped CeO2 thin films whereas pure CeO2 thin films exhibit paramagnetic behavior. The enhanced magnetic properties are attributed to formation of that complex between the Mn ion and an oxygen vacancy which is confirmed by XPS analyses.